Generalized solutions for singular double-phase elliptic equations under mixed boundary conditions - Jian Liu; Zengqin Zhao (Nonlinear Analysis)
In this article, we investigate at least one or two generalized solutions for double-phase singular elliptic equations with Hardy potential. We show the existence of at least one or two distinct generalized solutions under mixed boundary conditions via variational methods when the nonlinearity f satisfying suitable hypotheses.